Electrochemical, Spectroelectrochemical, and Electrocatalytic Dioxygen Reducing Properties of Peripheral Tetra-2,6-dimethoxyphenoxy Substituted Phthalocyanines - ÖZKAYA, ALİ RIZA; ORMAN, EFE BATURHAN; ODABAŞ, ZAFER (WILEY-V C H VERLAG GMBH, 2021)
By using of peripherally tetrakis-2,6-dimethoxyphenoxy substituted Co(II), Fe(III), and Mn(III) phthalocyanines was observed to extend the redox richness of the phthalocyanine ring with the addition of reversible metal-based electron transfer couples to the phthalocyanine ring-based electron transfer processes in solution. The emergence of highly steady anionic and cationic redox species with clear spectral and colour changes both in solution and in the film during in situ spectroelectrochemical and in situ electrocolorimetric measurements pointed out their applicability as electrochromic materials. Furthermore, the phthalocyanine complexes demonstrated strong interaction with dioxygen and thus, high electrocatalytic enforcement for its reduction.
Keywords: Metallophthalocyanines; Electrochemistry; Electrocatalysis; Oxygen Reduction; Methanol-tolerant catalyst; METAL-FREE; MANGANESE PHTHALOCYANINE; PHOTOCHEMICAL PROPERTIES; OXYGEN; COBALT; CO(II); REDUCTION; CATALYSTS; ZN(II); CU(II)